WORKSHOP PENULISAN KARYA ILMIAH SEBAGAI UPAYA PENGEMBANGAN PROFESIONALISME GURU SMK - Wening, dkk, Sri (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
Abstract The objectives of community service activity through scientific writing workshop for vocational high school (SMK) teachers are: 1) to increase professionalism development of SMK teachers to fulfill promotion requirement; 2) to increase capability of making and presentation scientific writing product; and 3) to produce scientific writing product that ready to publish. The activities of scientific writing workshop was done by 54 teachers of SMKN 2 Godean. Workshop activities were done by using method: 1) discourse about scientific writing, scientific writing ethics, scientific writing technique, language in scientific writing, reference scanning through internet, making scientific writing, and self-editing technique; 2) discussion at every matter submitted, participant can dialogue and discuss with team; 3) task to make scientific product which to obtain certificate requirement. Making of scientific product was conducted by tutorial. The community service activity through scientific writing workshop can be concluded successfully. It can be showed from positive response of participant from target of 65 participants can be realized become 54 participants or 83% at workshop implementation. Besides that the teachers gets attachment of knowledge and skill in reference scanning through internet access. However, target of the many scientific product that ready to publish is unattainable because the teachers have not motivation to write scientific product and the many activities of teacher in school. Keywords: profesionalisme, teachers, workshop, and scientific writing